2012
DOI: 10.1007/s00246-012-0403-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Resource Use for Infants With Hypoplastic Left Heart Syndrome During Bidirectional Glenn: Summary From the Joint Council for Congenital Heart Disease National Pediatric Cardiology Quality Improvement Collaborative Registry

Abstract: The National Pediatric Cardiology Quality Improvement Collaborative (NPC-QIC) registry captures information on interstage management of infants with hypoplastic left heart syndrome (HLHS). The purpose of this study was to identify interstage risk factors for increased resource use and adverse outcomes during bidirectional Glenn (BDG) hospitalization. All infants in the NPC-QIC registry (31 United States hospitals) undergoing BDG surgery were included (December 2009 to August 2010). Patient demographics, inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 16 publications
4
27
0
Order By: Relevance
“…The median hospital LOS was 8 days, consistent with several previous single center reports 58,12,2325 , although some series have reported considerably longer LOS ranging from 11 to 21 days 13,26 . Given this wide variability in LOS in the published literature, it is not surprising that there was a significant association of LOS with the surgical center at which the stage II procedure was performed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The median hospital LOS was 8 days, consistent with several previous single center reports 58,12,2325 , although some series have reported considerably longer LOS ranging from 11 to 21 days 13,26 . Given this wide variability in LOS in the published literature, it is not surprising that there was a significant association of LOS with the surgical center at which the stage II procedure was performed.…”
Section: Discussionsupporting
confidence: 88%
“…This approach reduces morbidity and mortality at the time of the Fontan procedure 1,2 and is well tolerated Several series suggest the median length of hospital stay (LOS) is 5–7 days and there are relatively few complications 38 . Despite the generally excellent results there are a number of preoperative risk factors associated with prolonged LOS, hospital death, or failure of the cavopulmonary circulation to provide adequate oxygenation and/or acceptable hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts currently are underway in the multicenter National Pediatric Cardiology Quality Improvement Collaborative to refine predictors of risk for individual patients and to identify specific practices associated with improved interstage survival and lower admission rates. [23][24][25] FIGURE E1. When there were clinical concerns from either the parent or the NP, an action plan was created.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that lower weight-for-age z -scores increase the risk of complications after S2P [1, 33]. More recently, Anderson et al [2] demonstrated that non-Caucasian races have lower weight-for-age z -scores.…”
Section: Discussionmentioning
confidence: 99%